TEORI PERKEMBANGAN KOGNITIF JEAN PIAGET DAN PROBLEMATIKANYA PADA ANAK USIA SEKOLAH DASAR - Leny Marinda (An-Nisa' Journal of Gender Studies, 2020)
Cognitive development is a change processes of human life in understanding, managing information, solving problems and knowing something. Jean Piaget is one of a figures studied cognitive development and said about cognitive development steps. Jean Piaget is also a biologist who links the physical maturity development with cognitive development steps. These steps are the motoric sensory step (0–2 years), pre-operational (2-7 years), concrete operations (7–11 years) and formal operations (11–15 years). In understanding the world actively, a child uses a scheme, assimilation, accommodation, organization and equilibration. A child's knowledge formed gradually in line with the information experience found. According to Piaget, children undergo a definite sequence of cognitive development steps. In this theory, children predicted to have maturity quantity and quality based on the steps passed. a step of cognitive development is a continuation of previous cognitive development. Cognitive problems arise in elementary school children viewed from Piaget's cognitive development theory including dyslexia, dysgraphia and dyscalculia. Perkembangan kognitif adalah tahapan-tahapan perubahan yang terjadi dalam rentang kehidupan manusia untuk memahami, mengolah informasi, memecahkan masalah dan mengetahui sesuatu. Jean Piaget adalah salah satu tokoh yang meneliti tentang perkembangan kognitif dan mengemukakan tahapan-tahapan perkembangan kognitif. Jean Piaget yang juga ahli Biologi menghubungkan tahapan perkembangan kematangan fisik dengan tahapan perkembangan kognitif. Tahapan-tahapan tersebut adalah tahap sensory motorik (0–2 tahun), pra-operasional (2–7 tahun), operasional konkret (7–11 tahun) dan operasional formal (11–15 tahun). Dalam memahami dunia secara aktif, anak menggunakan skema, asimilasi, akomodasi, organisasi dan equilibrasi. Pengetahuan anak terbentuk secara berangsur sejalan dengan pengalaman tentang informasi-informasi yang ditemui. Menurut Piaget, anak menjalani urutan yang sudah pasti dari tahap-tahap perkembangan kognitif. Pada teori ini, anak diprediksi memiliki kematangan secara kuantitas maupun kualitas berdasarkan tahapan-tahapan yang dilaluinya. Perkembangan kognitif pada satu tahap merupakan lanjutan dari perkembangan kognitif tahap sebelumnya. Problem kognitif yang muncul pada anak usia sekolah dasar dilihat dari teori perkembangan kognitif ala Piaget diantaranya disleksia, disgrafia dan diskalkulia.